ANALYSIS OF PHYSICAL AND CHEMICAL CHARACTERISTIC OF FLUID IN HOT SPRINGS IN TALAWAAN BANTIK VILLAGE, WORI DISTICT - Makahinda, Florstin Celine; Wenas, Donny R.; Sompotan, Armstrong F. (LPPM Politeknik Saint Paul Sorong, 2025)
Geothermal is a natural heat resource derived from the interaction between heat that has been emitted by hot rocks and water. Geothermal energy is pollution-free, sustainable, or renewable. Geothermal energy appears on the surface in the form of geothermal manifestations such as warm ground, steamy ground, hot springs. North Sulawesi has the potential to be the location of direct and indirect geothermal development. This study aims to determine the fluid type and molecular functional groups of hot springs in Sawangan Village, North Minahasa Regency, because this location has geothermal potential. By using the geochemical method of making diagrams , it is known that the fluid type of hot springs in Talawaan Bantik Village, Wori District is of the Birkabonat type and the molecular functional groups are C = O and O-H, where the parent chain, C, O and H bind (Bicarbonate) which corresponds to the fluid type results.